Aluminum tolerance in castor bean lines - Freitas, Lucas Barbosa de [UNESP]; Fernandes, Dirceu Maximino [UNESP]; Mendonca Maia, Suelen Cristina; Pivetta, Laerte Gustavo; Zanotto, Mauricio Dutra [UNESP] (Univ Federal Goias, 2018)
Castor bean plants are susceptible to aluminum (Al) in the soil, requiring adequate management techniques for their cultivation in acid soils containing high Al levels, as it occurs in tropical regions. This study aimed to assess the Al tolerance of castor bean lines. A randomized block design, in a 2 x 9 factorial scheme, with four replicates, was used. The treatments consisted of presence and absence of Al, as well as nine castor bean lines (CRZ H06, CRZ H11, CRZ H12,CRZ H15,CRZ H17,CRZ H18, CRZ H19, CRZ H22 and FCA). Based on a distribution into quartiles, the lines were divided into two groups. The Al-tolerant group contained the CRZ H06, H11 and H17 lines, while the group susceptible to Al was composed of CRZ H12, H15, H18, H19, H22 and FCA. The FCA and CRZ H17 lines showed the highest growth, when cultivated without Al.